Kurt Hahn inspirational, visionary, outdoor and experiential educator - Veevers, Nick; Allison, Pete.; SpringerLink (Online service). (Rotterdam Boston SensePublishers, 2011)
Kurt Hahn had a huge influence on the fields of outdoor and experiential learning, adventure education and, not least, badge schemes (Gordonstoun, Moray, and County Badges; and Duke of Edinburgh Award) throughout the world. This book provides a detailed historical account, centred on Hahn and the movement which surrounded him, of the early development of adventure education up to 1944. This includes an examination of themes present throughout Hahn{u2019}s educational endeavours. It looks at Hahn{u2019}s founding of Salem School (Germany) in 1920 and then Gordonstoun School (Scotland) in 1934. At both of these fee-paying schools activities such as sailing and hill-walking, often through expeditions lasting more than one day, played a prominent role in the education of the students. At Gordonstoun Hahn expanded his educational ventures, through the use of badge schemes, to include young people from the surrounding district who were not students at his school. Hahn expanded his badge schemes, firstly across the county in which Gordonstoun was situated, Morayshire, and then across Britain. The Outward Bound Sea School was founded by Hahn and Lawrence Holt, a ship-owner, at Aberdovey (Wales) in October 1941. It was a training centre where students could go for four week courses and it followed the badge scheme syllabus. During this period Hahn{u2019}s educational vision was one of those that influenced the Norwood Report and consequently the 1944 Education Act in terms of outdoor activities. This act provided the framework within which Outdoor Centres were set up by Local Education Authorities in the UK. This book looks at the various contexts, which came together through Hahn, and which help the reader understand his actions: German educational practice; Hahn{u2019}s and Prince Max{u2019}s (owner of Salem School) experiences of the First World War and its aftermath and the need to educate people to speak out and act upon their convictions; Hahn{u2019}s and Prince Max{u2019}s inclusive agenda; British educational practice; the Second World War; and Hahn{u2019}s expansionist aims. Kurt Hahn was one of the field{u2019}s greatest advocates and this book provides a detailed historical examination of his work and brings light to the complex tapestry of events which led to the rise and development of adventure education. - Publisher's description.
Electronic reproduction.
Keywords: Hahn, Kurt -- 1886-; Education -- Philosophy; Outward bound schools -- History; Outdoor education -- History; Educators -- Germany -- Biography; Electronic books